Research progress in integrated groundwater-surface water models - Shuyan PENG; Zheng LU; Tingting WU; Xiaofan YANG (Shuiwen dizhi gongcheng dizhi)
Groundwater-surface water interaction involves material transport and energy transfer processes, which directly impacts the hydro-ecological environment of watersheds. It is a crucial component of the hydrological cycle which has become a hot issue in hydrogeology in recent years. The integrated groundwater-surface water models serve as a powerful tool for studying groundwater-surface water interaction. This paper reviewed recent studies on integrated groundwater-surface water models, providing an overview in five aspects: classification of integrated groundwater-surface water models, sources of model bias, model application, challenges, and trend of model development. Integrated models are categorized into fully coupled and loosely coupled models based on coupling schemes. There are five categories of sources of integrated model bias, including topographic processing, meteorological forcing bias, model parameters, anthropogenic process, and epistemic limitations. The integrated models are widely used to study the changes in groundwater-surface water patterns under the influences of climate change and human activities, and to research water resources management and optimization. In addition, the integrated models are facing multiple challenges, such as the increasing demand for basic data, higher requirements for hardware platforms, the difficulty in accurately determining the modeling region, and the evident trend of interdisciplinary integration. Finally, the integrated model development is expected to focus on enriching the approaches to obtaining model parameters, improving the simulation efficiency, and strengthening the integration of model coupling with different disciplines.